Differentiator-Based Incremental Three-Dimensional Terminal Angle Guidance With Enhanced Robustness - Han, Tuo; Shin, Hyo-Sang; Hu, Qinglei; Tsourdos, Antonios; Xin, Ming (IEEE transactions on aerospace and electronic systems, 2022)
In this article, an incremental guidancelaw with terminal angle constraint is proposed against maneuvering targets in the 3-D space. First, a sliding surface is constructed such that its first-order dynamics excludes the relative range and line-of-sight angles in the perturbation. This manipulation avoids unboundedperturbations induced by target maneuvers near collision. Then, a benchmark guidance law is derived via the nonlinear dynamic inversion (NDI) based sliding mode control (NDI-SMC). To further enhance guidance system robustness, an incremental nonlinear dynamic inversion (INDI) based SMC (INDI-SMC) 3-D guidance law is developed. The INDI-SMC guidance law exploits the first-order derivative of the sliding variable and guidance command output at the latest step, which leads to reduced perturbation and thus requires smaller gains than the NDI-SMC guidance law. A multivariable continuous differentiator is employed to estimate the sliding variable's first-order derivative for guidance law implementation. Moreover, the stability of the differentiator is analyzed and the guidance robustness under uncertainties is compared. Extensive numerical simulations and a Monte Carlo test are conducted to verify effectiveness and robustness of the proposed method.